The Magic Pill: A Qualitative Study of Relational Leadership, Leader Feedback, and Teacher Attrition in Georgia - Burt, Nila (My University, 2022)
New teachers are leaving the profession at steadily increasing rates at a substantial cost to Georgia taxpayers who support local school districts and the state department of education (Pelfrey, 2020). Recruitment, training, and hiring efforts are examples of these cost burdens. Teacher turnover causes educational losses for students and financial strains for communities (Owens, 2015; Tran & Smith, 2020). Forty-four percent of teachers leave the field within their first five years, and two-thirds of current teachers do not recommend the profession to others (Georgia Department of Education, 2015). This study examined new teachers’ perceptions of the influence of leadership style on school climate and new teachers’ decisions to remain in the profession through school administrators’ use of leader feedback. An interpretive qualitative research approach was applied to examine five new teacher participants’ lived experiences through narrative inquiry under the lens of the Relational Leadership Theory. Data were analyzed and triangulated through semi-structured interviews, data from the Georgia Department of Education’s tool for teacher performance feedback, and observations of teachers and the school’s social media. The findings revealed how relational leadership supported new teachers but did not reveal that the application of leader feedback influenced decisions for attrition. They also indicated that teachers entering the profession during the Covid-19 pandemic needed additional leader feedback on professional growth, classroom management strategies, and instructional practices. Additionally, this study shows the need for school leaders to be mindful of timely, personalized, frequent feedback and emotional support for Millennial and Generation Z teachers. Keywords: Relational Leadership, Generation Z, Teacher Attrition, Relational Leadership Theory, TKES, Culture and Climate
Chapter I--Overview 1 -- Problem Statement 3 -- Purpose of the study 4 -- Research Questions 4 -- Significance of the Study 5 -- Theoretical Framework 6 -- Conceptual Map 8 -- Research Methodology 9 -- Limitations 9 -- Summary 10 -- Definition of Terms 10 -- Chapter II--Literature Review 16 -- Theoretical Framework 21 -- Culture and Climate 27 -- Millennials and Generation Z 33 -- Teacher Assessment, Evaluation, and Feedback 36 -- Conclusion 45 -- Chapter III--Methodology 47 -- Research Design and Rationale 48 -- Setting 51 -- Role of the Researcher 54 -- Participant Sampling and Selection 54 -- Qualitative Methods of Data Collection 56 -- Interview Process 56 -- Georgia Leader Performance Model 58 -- Observations and Social-Media 58 -- Data Analysis Procedures 59 -- Credibility 61 -- Researcher Bias 62 -- Transferability 62 -- Dependability 63 -- Confirmability 64 -- Ethical Considerations 64 -- Institutional Review Boards 65 -- Informed Consent and Confidentiality 65 -- Summary 65 -- Chapter IV—Participant Profiles 67 -- Background of Participants 68 -- James 69 -- Sam 74 -- Holly 84 -- Sara 91 -- Joe 102 -- Summary 106 -- Chapter V—Discussion of Themes 109 -- Data Analysis 110 -- Background 112 -- Theme One—Relational Experiences and Classroom Supports 115 -- Theme Two—School Climate and Teacher Success 129 -- Theme Three—Administrative Presence and Feedback Frequency 142 -- Chapter Summary 149 -- Chapter VI—Summary, Conclusions, and Recommendations 151 -- Research Questions: Summary 153 -- Implication and Discussion 162 -- Limitations of the Study 164 -- Recommendations for Future Research 165 -- Conclusions 166 -- References 171 -- Appendix A: Interview Questions 181 -- Appendix B: Application for Use of Human Participants in Research 184 -- Appendix C: Research Statement of Consent 186 -- Appendix D: Collaborative Institutional Training Initiative 188
Keywords: Dissertations, Academic--United States; Education; Educational evaluation; Educational philosophy